FORMATION OF STUDENTS' RELIGIOUS CHARACTER THROUGH RELIGIOUS HABITUATION ACTIVITIES AT MIS AL-MAHDIYYIN KADUNGORA at MIS Al-Mahdiyyin Kadungora - Khairunisa Nurkhasanah; Munawar Rahmat; Muhamad Parhan (PIONIR: JURNAL PENDIDIKAN, 2025)
The formation of religious character in children is a systematic process that involves education that focuses not only on religious knowledge, but also on the appreciation and practice of spiritual values in various aspects of life. The purpose of this study is to describe the habituation activities carried out daily to form students' religious character and analyze the inhibiting and supporting factors of the process of forming students' character at MIS Al-Mahdiyyin. This research uses qualitative research methods with the type of field research and data collection techniques through observation, interviews and documentation. The results of this study show that religious habituation that is consistently carried out every day has a positive impact on the formation of students' character. Factors that support the achievement of religious character in students include the role of teachers and adequate school facilities to carry out activities. As a follow-up, for further research, it is recommended that researchers prepare more mature time planning and expand the search for literature from various sources including international journals and current research. Keywords: Character, Habituation, Religious